21q22 amplification detection in three patients with acute myeloid leukemia: cytogenomic profiling and literature review - Emily M. Kudalkar; Changlee Pang; Mary M. Haag; Daniel A. Pollyea; Manali Kamdar; Gang Xu; Meng Su; Billie Carstens; Karen Swisshelm; Liming Bao (Molecular Cytogenetics, 2022)
Abstract Background 21q22 amplification is a rare cytogenetic aberration in acute myeloid leukemia (AML). So far, the cytogenomic and molecular features and clinical correlation of 21q22 amplification in AML have not been well-characterized. Case presentation Here, we describe a case series of three AML patients with amplified 21q22 identified by fluorescence in situ hybridization using a RUNX1 probe. Two of these patients presented with therapy-related AML (t-AML) secondary to chemotherapy, while the third had de novo AML. There was one case each of FAB M0, M1 and M4. Morphologic evidence of dysplasia was identified in both t-AML cases. Phenotypic abnormalities of the myeloblasts were frequently observed. Extra copies of 21q22 were present on chromosome 21 and at least one other chromosome in two cases. Two showed a highly complex karyotype. Microarray analysis of 21q22 amplification in one case demonstrated alternating levels of high copy number gain split within the RUNX1 locus at 21q22. The same patient also had mutated TP53. Two patients died at 1.5 and 11 months post-treatment, while the third elected palliative care and died within 2 weeks. Conclusions Our results provide further evidence that 21q22 amplification in AML is associated with complex karyotypes, TP53 aberrations, and poor outcomes. Furthermore, we demonstrate that 21q22 amplification is not always intrachromosomally localized to chromosome 21 and could be a result of structural aberrations involving 21q22 and other chromosomes.